A case of infectious mononucleosis caused by Epstein-Barr virus complicated by autoimmune hemolytic anemia - R. F. Sayfullin; K. E. Abdieva; A. V. Razumeykina; A. P. Zolotareva; O. A. Ivanova (Детские инфекции (Москва))
We represent a rare clinical case of infectious mononucleosis with hepatitis, caused by Epstein-Barr virus, complicated by rare secondary autoimmune hemolytic anemia associated with warm agglutinins in a 16-year-old patient. The disease was long-lasting, with a two-wave course of febrile fever. Signs of hepatitis with the development of anemia of moderate severity appeared during the second wave of febrile fever. The etiology of the disease was confirmed by the detection of Epstein-Barr virus DNA in blood and the detection of anti-VCA IgM antibodies to Epstein-Barr virus in the absence of anti-EBNA IgG antibodies. Hemolytic anemia was verified using markers of hemolysis (increased lactate dehydrogenase activity, decreased haptoglobin concentration), and positive results of a direct Coombs test. After successful initiation of prednisone therapy and clinical improvement, the patient was discharged from the hospital on the 24th day of disease to continue treatment on an outpatient basis (prednisone was replaced by methylprednisolone).This case demonstrates the development of a rare autoimmune complication in infectious mononucleosis caused by the Epstein-Barr virus.